Extracorporeal Life Support as a Treatment of Supraventricular Tachycardia in a Newborn. Issue 2 (February 2021) - Matsudo, Takahiro; Tsuboi, Norihiko; Nishimura, Nao; Nakagawa, Satoshi
Abstract : Abstract: Supraventricular tachycardia (SVT) is the most common symptomatic tachyarrhythmia in children and requires medical treatment. Thus far, there have been few reports of the use of extracorporeal life support (ECLS) to provide cardiac support in children with low cardiac output resulting from arrhythmia. We present a case of a newborn in whom ECLS was used to provide support for cardiogenic shock secondary to intractable SVT. A 25-day-old girl presented with a 5-hour history of increasing pallor and listlessness. A clinical examination at presentation revealed retractions and peripheral coldness. An electrocardiogram showed a narrow-QRS tachycardia with a rate of 290 beats per minute. Adenosine triphosphate (maximum, 0.2 mg/kg) and synchronous direct current shock (maximum, 25 J) were ineffective. Chest x-ray showed a cardiac dilatation, and echocardiography showed a structurally normal heart with very poor function. The cardiogenic shock caused by SVT was refractory to treatment. The low cardiac output state persisted with worsening metabolic acidosis (bicarbonate, 5.8 mEq/L; lactate, 14.3 mmol/L). In view of the intractable tachyarrhythmia and worsening perfusion, blood access catheters were inserted, and ECLS was initiated. After commencing ECLS support, intravenous adenosine triphosphate (1.25 mg/kg) was administrated. The patient then reverted to a sinus rhythm with a rate of 180 beats per minute. There was considerable improvement of the heart function within 2 days of starting ECLS; the patient was weaned from ECLS support, and the blood access catheters were decannulated on day 3. After weaning from ECLS support, cardiac function returned to normal.